The Effect of Human Resource Ethics on Financial Reporting Implications for Good Government Governance (Survey of related sub-units in State-Owned Enterprises in SUMSEL) - Hertati, Lesi; Zarkasyih, Wahyudin; Suharman, Harry; Umar, Haryono (International Journal of Economics and Financial Issues, 2019)
Human resource ethics is needed for quality decision making. Thus, the ethics of quality human resources financial reporting is produced by good human resource ethics. The purpose of this study was to determine the effect of Human Resource Ethics on Financial Reporting Implications on Good Government Governance. The unit of analysis in this study is the related sub-units in State-Owned Enterprises in Indonesia. The population of this study is 335 related sub-units in BUMN. Using SEM-LISREL as an analytical tool. Data was collected by questionnaire as a research instrument. Results have shown that financial reporting can be reflected through: 1) responsibility, 2) accountability, 3) liability. Keywords: Human Resource Ethics, Financial Reporting, Good Government Governance JEL Classifications: G3, G23, O15 DOI: https://doi.org/10.32479/ijefi.8466